DAMPAK MANAJEMEN ASET DAN MANAJEMEN UTANG TERHADAP LIKUIDITAS DAN PROFITABILITAS BUMN TERDAFTAR DI BURSA EFEK INDONESIA - Firizq, Nur Kamiliyah; Rahmiyati, Nekky; Ratnawati, Tri (JMM17 : Jurnal Ilmu ekonomi dan manajemen, 2019)
The purpose of this study was to determine the impact of asset management and debt management on the liquidity and profitability of SOEs listed on the Indonesia Stock Exchange for the period 2014-2017. This study use the object of research as 16 BUMN companies. The data source used is secondary data, data collection techniques in this study are documentation of company performance reports on the Indonesia Stock Exchange and company annual reports. The results of the study show that the relationship between asset management and debt management is directly proportional. There is no significant impact of asset management on liquidity and profitability because the asset management on 2017 has increased while profitability and liquidity has fallen this is due to the company's large operational costs financed by debt. Debt management for liquidity and profitability has an impact on decreasing liquidity and profitability when debt management rises. Keywords: Liquidity, Asset Management, Debt Management and Profitability